2020
DOI: 10.3390/ani10040677
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Aflatoxin B1-Induced ROS Formation and Increase of m6A RNA Methylation

Abstract: Aflatoxin B1 (AFB1) is one of the most dangerous mycotoxins in both humans and animals. Regulation of resveratrol is essential for the inhibition of AFB1-induced oxidative stress and liver injury. Whether N6-methyladenosine (m6A) mRNA methylation participates in the crosstalk between resveratrol and AFB1 is unclear. The objective of this study was to investigate the effects of AFB1 and resveratrol in m6A RNA methylation and their crosstalk in the regulation of hepatic function in mice. Thirty-two C57BL/6J male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
(87 reference statements)
1
26
0
Order By: Relevance
“…Wu et al ( Stoneley and Willis, 2004 ) showed that compared with normal mice, aflatoxin-treated mice had increased ROS levels, which in turn led to the increased expression of the MT METTL3 and the decreased expression of the demethylase FTO in the liver tissue of mice treated with ROS; therefore, the m6A modification of related RNA, such as B-cell lymphoma 2 (Bcl-2), cysteine aspartyl-specific protease (caspase)-3, and Bcl-2-associated X protein (Bax), increased, thus participating in the pathological process of liver injury. Studies have shown that resveratrol may reverse ROS-induced liver injury caused by aflatoxin by reducing RNA methylation ( Wu et al, 2020 ; Ko et al, 2017 ). Zhao et al (2019) confirmed that arsenous-acid-induced oxidative stress can affect the expression levels of m6A MT and demethylases, especially the expression levels of WTAP and METTL14, thereby regulating the m6A modification of genetic polymorphisms of C12orf51 (HECTD4), ATP-binding cassette transporter A5 (ABCA5), solute carrier family 22 member 17 (SLC22 A17) and potassium voltage-gated channel subfamily Q member 5 (KCNQ5) genes and influencing the transcription and translation of the genes, thus participating in subsequent pathophysiological processes.…”
Section: Atherosclerosis and The M6a Ribonucleic Acid Modificationmentioning
confidence: 99%
“…Wu et al ( Stoneley and Willis, 2004 ) showed that compared with normal mice, aflatoxin-treated mice had increased ROS levels, which in turn led to the increased expression of the MT METTL3 and the decreased expression of the demethylase FTO in the liver tissue of mice treated with ROS; therefore, the m6A modification of related RNA, such as B-cell lymphoma 2 (Bcl-2), cysteine aspartyl-specific protease (caspase)-3, and Bcl-2-associated X protein (Bax), increased, thus participating in the pathological process of liver injury. Studies have shown that resveratrol may reverse ROS-induced liver injury caused by aflatoxin by reducing RNA methylation ( Wu et al, 2020 ; Ko et al, 2017 ). Zhao et al (2019) confirmed that arsenous-acid-induced oxidative stress can affect the expression levels of m6A MT and demethylases, especially the expression levels of WTAP and METTL14, thereby regulating the m6A modification of genetic polymorphisms of C12orf51 (HECTD4), ATP-binding cassette transporter A5 (ABCA5), solute carrier family 22 member 17 (SLC22 A17) and potassium voltage-gated channel subfamily Q member 5 (KCNQ5) genes and influencing the transcription and translation of the genes, thus participating in subsequent pathophysiological processes.…”
Section: Atherosclerosis and The M6a Ribonucleic Acid Modificationmentioning
confidence: 99%
“…In alcohol-AFB1-induced rat hepatocellular carcinoma, a two-week treatment with R (100 mg/kg bw) restored the level of key antioxidant enzymes (i.e., SIRT1, CAT, and GPX) toward normal levels [ 30 , 58 ]. In mice, R decreased AFB1-induced ROS accumulation, ameliorated adverse hepatic functions by increasing hepatic antioxidant capacity and inhibiting the expression of cleaved-caspase-3 protein [ 59 ]. Likewise, in Sprague Dawley rats fed AFB1 (7.5 μg/200 g), R effectively prevented the AFB1-induced testicular damage and lipid peroxidation [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of them can lead to the downregulation of the level of m 6 A [275]. Another study had shown that resveratrol can reducing the ROS accumulation induced by mycotoxin Aflatoxin B1 thereby decreasing m 6 A-modified RNA levels [276]. These results exhibit the association between oxidative stress and m 6 A modification.…”
Section: Role Of Oxidative Stress and M 6 A Modification In Cancermentioning
confidence: 91%